Importance of internal factors for community-managed water and wastewater systems in Cochabamba, Bolivia. Issue 6 (1st November 2020) - Helgegren, Ida; McConville, Jennifer; Landaeta, Graciela; Rauch, Sebastien
ABSTRACT: Community management is often seen as part of the solution to increase access to drinking water and wastewater management where municipal services are lacking. This article intends to increase the knowledge regarding self-organized community-managed water and wastewater systems in urban and peri-urban areas. A theory-building case-study approach, including three different neighbourhoods in Bolivia and their respective community-based organizations, was selected. Four prerequisites – leadership, agreed vision, collective action and management – and associated enabling factors connected to three distinct planning and management phases were found to be of major importance for community-managed water and wastewater systems.